Pengaruh Thin Capitalization, Financial Pressure dan Capital Intensity terhadap Tax Avoidance - Muhammad Syahrul Kahfi Adam; Imar Halimah (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Tax avoidance remains a significant concern for governments as it reduces potential state revenue and undermines fair taxation principles. This study aims to empirically and systematically examine the effect of thin capitalization, financial pressure, and capital intensity on tax avoidance. The research focuses on companies listed on the Indonesia Stock Exchange (IDX) in the basic materials sector from 2019 to 2023. Out of 110 companies, a purposive sampling method was used to select 26 companies that met specific criteria, resulting in 130 firm-year observations over a five-year period. The panel data regression model was employed and analyzed using EViews 13 software. The findings indicate that, both partially and simultaneously, the independent variables thin capitalization, financial pressure, and capital intensity significantly influence tax avoidance. These results highlight how corporate financial strategies and structures can impact tax planning behavior. The study provides important implications for tax authorities in improving monitoring and regulatory efforts to mitigate aggressive tax avoidance practices among corporations.